Motivation and Lifestyle of Millennial Tourists Visiting the Coffee Shop in Kintamani - Wiramatika, I Gede; Sumardani, Rizki (Jurnal Manajemen Pelayanan Hotel, 2023)
Coffee shop was originally a place to drink coffee quickly. Along with the times and the increasing number of customer interests, the development of the coffee shop in Kintamani is still happening today. At this time drinking coffee has become part of the lifestyle or modern lifestyle of millennial tourists. Many millennial tourists come to visit coffee shops in Kintamani not just to taste the taste of the coffee itself but to spend their free time and relax in a comfortable place and can calm the mind. This study aims to find out more about the motivation of millennial tourists to choose coffee shops in Kintamani as a place to fill their vacation time, the trend of coffee being a lifestyle for millennial tourists, in coffee shops in Kintamani. This research is a qualitative research, with research locations conducted in coffee shops in Kintamani. The data in this research were collected through observation, interviews, with the technique of determining the informants in this study using accidental sampling and the informants were taken from several coffee shops in Kintamani, and the data were analyzed using descriptive qualitative data analysis. The results of this study indicate that there are several things that motivate millennial tourists to come to coffee shops in Kintamani, namely close friends, area of origin, curiosity, getting out of routine, accessibility, internet network, affordable prices. From this, the existence of coffee shops is very popular because there is a comfortable place, a concept that makes millennial tourists interested in visiting coffee shops and drinking coffee has become a life style for millennial tourists. Keywords: Millennial tourists, motivation, lifestyle